Autocatalytic Ni-P and Ni-B deposition on SiC powders - Sezen, Gokce; Kilicarslan, Ayfer; Daglilar, Sibel; Kerti, Isil (ICE PUBLISHING, 2016)
Ceramic particles such as silicon carbide (SiC) have attracted great attention because of their usability as reinforcement for composite materials. Autocatalytic (electroless) nickel deposition is an excellent process for the enhancement of surface properties of ceramic particles. In this study, deposition of nickel-phosphorus (Ni-P) and nickel-boron (Ni-B) layer on SiC particles by way of autocatalytic plating in hypophosphite and borohydride baths was investigated. SiC powders were sensitised and activated respectively in order to ensure catalytic properties. Electroless nickel coating was performed from two different nickel ion sources ( nickel chloride, nickel sulfate) following the pretreatments of particle surfaces. Coated powder morphologies were characterised by scanning electron microscopy. Energy-dispersive spectroscopy analysis was used to investigate the chemical analysis of coatings. The results showed that a better uniformity and bonding were obtained for Ni-P coatings with the Ni2+ source of NiSO4.6H(2)O as compared to NiCl2.6H(2)O. For Ni-B coatings, the Ni2+ source of NiCl2.6H(2)O has provided better quality and continuous coating layer on SiC surfaces.
Keywords: coatings; morphology; surface; ATOMIC LAYER DEPOSITION; MATRIX COMPOSITES; PARTICLES; NICKEL; NANOPARTICLES; FABRICATION; RESISTANCE; CARBIDE; COPPER; Materials Science